Aqua-DST Validation Workshop – Myitkyina, Myanmar - Win, Shelly; Myint, Aye Chan; Buisson, Marie-Charlotte; de Silva, Sanjiv (International Water Management Institute, 2025)
The Aqua-DST Validation Workshop held in Myitkyina, Kachin State, brought together key stakeholders from the Department of Fisheries (DoF) and IWMI to validate and refine the full version of the Aquaculture Decision Support Tool (Aqua-DST). The tool, developed under the CGIAR Sustainable Animal and Aquatic Foods (SAAF) Program, uses multi-criteria suitability analysis to guide decision-making on small-scale aquaculture (SSA) and fishpond expansion across 170 townships in the Upper Ayeyarwady region. The workshop aimed to confirm the accuracy of model outputs, strengthen user understanding of the dashboard, and collect expert feedback to enhance the tool’s future applicability. A total of eight DoF officers (six women and two men) participated in hands-on activities covering suitability indicators, data structures, model functionality, and result interpretation. Participants explored the Aqua-DST dashboard, reviewed township-level suitability classifications, and compared model outputs with their field-based knowledge. Validation results showed strong alignment between the tool and local expertise for several townships, while adjustments were recommended for others, particularly where remoteness, limited infrastructure, or climatic constraints affect aquaculture potential. Stakeholders also provided region-specific insights on suitable fish species and preferred culturing methods, contributing to the refinement of the tool’s thematic layers. Participants highlighted several challenges affecting aquaculture development, including weak policy guidance, limited budgetary support, poor information-sharing systems, financing constraints, and reduced government engagement in conflict-affected areas. Data access issues and gaps in secondary datasets were also noted.